Tomato pomace as a nontraditional feedstuff: productive and reproductive performance, digestive enzymes, blood metabolites, and the deposition of carotenoids into egg yolk in quail breeders - Fayiz M. Reda; Mahmoud Madkour; Nafisa Abd El-Azeem; Osama Aboelazab; Sarah Y.A. Ahmed; Mahmoud Alagawany (Poultry Science, 2022)
ABSTRACT: This study aimed to evaluate the inclusion of tomato pomace (TP) into Japanese quail breeders' diet by investigating its effects on digestive enzymes, immune response, antioxidant status, blood biomarkers, productive performance, and the deposition of carotenoids into the egg yolk. A total of 150 mature 8-wk of age Japanese quails (100 females and 50 males) were allocated into 5 treatment groups, with 5 replicates, each of 6 quails (4 females and 2 males). The experimental diets were isoenergetic and isonitrogenous, based on corn and soybean meal, and included 0, 3, 6, 9, and 12% of tomato pomace, respectively. The results showed that dietary supplementation of tomato pomace up to 12% significantly improved the immune response, antioxidant response, and digestive enzymes of Japanese quail breeders, significantly decreased cholesterol, low-density lipoprotein (LDL), and increased high-density lipoprotein (HDL). Also, TP increased egg weight, egg mass and hatchability , where TP 6% had the greatest egg weight, egg mass and hatchability among other groups. Moreover, tomato pomace inclusion significantly had a positive effect on the deposition of lycopene into the egg yolk and it can be used as a good delivery system to improve human health. Tomato pomace up to 12% could be used as an alternative feedstuff in quail breeders' diets.